ANALYSING THE APPLICATION OF GOOD GOVERNANCE PRINCIPLES IN PUBLIC ADMINISTRATION - Loso Judijanto; Melyana R Pugu; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study aims to analyse the application of good governance principles in public administration and its impact on the effectiveness of public services and public trust. Good governance, which includes the principles of transparency, accountability, public participation, and responsibility, is identified as a key factor that can improve government performance. Through literature analysis and case studies, this research found that the application of good governance principles has a positive impact in reducing corruption, improving administrative efficiency, and strengthening the legitimacy of government policies. In addition, the research also revealed that active public participation in the decision-making process enriches policies with a more inclusive and relevant perspective. Accountability and transparency mechanisms have proven effective in building public trust and minimising abuse of power. The results show that public administrations managed based on the principles of good governance are better able to face complex development challenges with sustainable solutions.